Switching from a two‐tablet regimen of tenofovir/emtricitabine and efavirenz to a one‐tablet regimen may affect patients' perceptions and drug management1. Issue 5 (21st December 2015) - Rotzinger, A; Locatelli, I; Bugnon, O; Fayet Mello, A; Parienti, J‐J; Cavassini, M; Schneider, M.P
Abstract : Objectives: Simplification of antiretroviral therapy enhances a patient's adherence but a new formulation could also lead to new adverse events and changes in daily routine. This study compared medication adherence, tolerance and satisfaction among subjects switching from a two‐tablet tenofovir/emtricitabine/efavirenz regimen to a one‐tablet regimen. Methods: Clinical and sociodemographic data were collected and three surveys were administered at month 0 (=switch), and then 1 and 4–6 months after the switch: the Beliefs about Medicines Questionnaire, the HIV‐symptom index questionnaire, the Short HIV Treatment Satisfaction Questionnaire, the Swiss HIV Cohort Study (SHCS) two‐item adherence questionnaire, and a questionnaire on daily combination antiretroviral therapy (cART) management. Medication adherence of a subgroup of subjects was routinely monitored using an electronic device (MEMS ™ ). Results: Eighty‐eight subjects gave informed consent to participate in the study. The subjects' back‐switch rate was 7% (six of 88). Subjects who did not back‐switch preferred the one‐tablet regimen (median = 2; IQR = 1.3–2.5; on a −3 to 3 scale), but no change in adherence was found (10 of 46 nonadherent subjects; P = 1.00). The perception of treatment necessity score decreased ( P = 0.004), the efavirenz blood level increased (14%; P = 0.04), and association/dissociation of cART with food intake evolved ( P = 0.01) after the switch. Subjects listed equivalent numbers of symptoms during the three visits. Conclusions: The one‐tablet regimen was preferred but the number of back‐switches was not negligible. The perception of treatment necessity score decreased with the simplification of the regimen from a two‐tablet to a one‐tablet formulation, which could negatively impact adherence. Switching is a sensitive time in a patient's treatment life and professionals should pay particular attention to patient's perceptions of treatment during such a transition.